(untitled) (International Journal of Nursing Education, 2021)
Background: The aim of this study was to improve depression screening, monitoring, and treatment of individuals in community-based programs with co-morbid type 2 diabetes by senior nursing students. Method: This experimental research utilized the Basic Diabetes Knowledge Test (KAT), Depression Knowledge Questionnaire (MCQ), and the Patient Health Questionnaire -9 (PHQ-9) to measure the depression and diabetes knowledge of students before and after an educational intervention over time utilizing ANOVA. Results: The main effect of time for KAT and MCQ is statistically significant (F2=16.74, p<0.0001 for KAT and F2=10.39, p<0.0001 for MCQ). Adjusted KAT and MCQ scores t-tests were run across the test administrations to assess the PHQ-9 mean test score difference. Results: Indicate statistically significant differences between groups (t (72) =-2.82, p=0.0063). Conclusions: The findings of this research should compel nursing faculty to integrate teaching strategies in clinical courses to assist new nurses to adequately identify and refer individuals for depression evaluation and treatment.